Acquired erythropoietic protoporphyria: A systematic review of the literature. Issue 1 (21st August 2019) - Snast, Igor; Kaftory, Ran; Sherman, Shani; Edel, Yonatan; Hodak, Emmilia; Levi, Assi; Lapidoth, Moshe
Abstract: Background: Erythropoietic protoporphyria (EPP) is a semi‐dominantly inherited porphyria presenting with photosensitivity during early childhood. Acquired EPP has been reported; however, data regarding this rare disorder are scarce. Purpose: To evaluate the characteristics of acquired EPP. Methods: A comprehensive search of PubMed, Google Scholar, ScienceDirect, and clinicaltrials.gov databases was performed by three reviewers. Studies describing patients with acquired EPP were included. Additionally, we present an index case of a 26‐year‐old patient who acquired clinically and biochemically typical EPP in association with myelodysplastic syndrome (MDS). Results: We included 20 case reports describing 20 patients. Most (80%) patients were male of mean age 58 ± 13 years. In all patients, acquired EPP was associated with hematological disease, most commonly MDS (85%) followed by myeloproliferative disease (10%). In 86% of cases, hematological disease led to abnormality or somatic mutation in chromosome 18q (the locus of the ferrochelatase gene). The mean erythrocyte protoporphyrin IX concentration was very high (4286 μg/dL). Most (90%) patients presented with photosensitivity, 20% experienced blistering, and 25% presented with hepatic insufficiency, both uncommon in EPP. In 55% of patients, hematological disease was diagnosed after occurrence of cutaneous symptoms. Beta‐carotene led to partial control of symptoms in 5 patients and resolution in another patient. Azacitidine treatment of MDS led to resolution of cutaneous symptoms in three patients. Conclusion: We present the distinct features of acquired EPP and highlight that any patient presenting with new‐onset photosensitivity, irrespective of age should be evaluated for porphyria.